2019
DOI: 10.1038/s41467-019-11664-1
|View full text |Cite
|
Sign up to set email alerts
|

Early progression to active tuberculosis is a highly heritable trait driven by 3q23 in Peruvians

Abstract: Of the 1.8 billion people worldwide infected with Mycobacterium tuberculosis , 5–15% will develop active tuberculosis (TB). Approximately half will progress to active TB within the first 18 months after infection, presumably because they fail to mount an effective initial immune response. Here, in a genome-wide genetic study of early TB progression, we genotype 4002 active TB cases and their household contacts in Peru. We quantify genetic heritability ( ) of early TB progress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 59 publications
0
75
0
1
Order By: Relevance
“…A recent genetic study of early progression to TB disease (within 18 months) demonstrated that the genetic architecture of early progression and later reactivation disease are different (47).…”
Section: Discussionmentioning
confidence: 99%
“…A recent genetic study of early progression to TB disease (within 18 months) demonstrated that the genetic architecture of early progression and later reactivation disease are different (47).…”
Section: Discussionmentioning
confidence: 99%
“…Under Setting 1, regions spanning 5000 base pairs upstream and downstream of genes or SNPs associated with TB outcomes (reported by GWAS catalog [31], Open Targets[32], and other GWAS studies[33, 34, 35]) were considered. The killer cell immunoglobulin-like receptor (KIR) and human leukocyte antigen (HLA) gene regions were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…Here we investigate this hypothesis in a prospective cohort of 3,980 Peruvains 9 . The genome of contemporary Peruvians is shaped by extensive admixture between Native Peruvians and the Europeans, Africans, and Asians that arrived in Peru following colonization 1214 .…”
Section: Main Textmentioning
confidence: 99%
“…We observed nominal evidence of association at 3q23 (Wald test Wald test p-value = 2.8×10 −5 ), 2p24.3 (Wald test p-value = 5.9×10 −5 ), and 5p23.2 (Wald test p-value = 7.2×10 −5 , Figure S3 ). In a previous genome-wide association study (GWAS) our group showed that 3q23 locus is significantly associated with TB progression risk in Peruvians (p-value < 5×10 −8 ) 9 . In our GWAS, the top risk variant (rs73226617, OR = 1.18; p-value = 3.9×10 −8 ) at 3q23 has a higher frequency in Europeans compared to Peruvians (MAF = 0.05 vs. 0.03) and is unlikely to explain the admixture mapping signal we observe at this locus.…”
Section: Main Textmentioning
confidence: 99%